Sea level isobaric analysis by the method of optimum interpolation (MAUSAM, 1982)
A programme has been developed to obtain analysis of sea level pressure by the Gandin's optimum interpolation method (Balousev et at. 1968 and Gandin 1969). In this paper the method of optimum interpolation is described and the algorithm followed is given. Finally the result of analysis of sea level pressure field are presented. The programme is portable with adjustable grid size.